Fatores sociodemográficos e clínicos associados ao pé diabético dos pacientes atendidos no ambulatório de um hospital ensino - José, Denilson Pereira (2014)
Introduction: Diabetes mellitus is a chronic disease evidenced by hyperglycemia and one of the main symptoms includes the diabetic foot, which can lead to amputation thereby decreasing the survival of patients with diabetes. Objective: Identify sociodemographic and clinical factors of patients with diabetes types one and two who were seen at the diabetic foot outpatient clinic at a University Hospital in São José do Rio Preto/SP. Methods: Descriptive study with a quantitative approach which the data was collected from 121(100%) electronic patient records with diabetes type 1 and 2 who were seen at the diabetic foot outpatient clinic at a University Hospital in São José do Rio Preto/SP from July 2010 to July 2012. Results: Of the 121 patients, 80(66,12%) were male,50(41,32%) were from São José do Rio Preto,46(38,02%) had incomplete primary education and, 86(71,07%) consensual marriage, with a mean age of 54,17 (DP=15,37) years old, since the age ranges from 21 to 84 years old.. As for the clinical characteristics, there is a majority of type 2 DM with 68(72,34%), showed presence of wounds 61(6,19%), 53(43,80%) of Wagner classification grade 0 (high risk, but no lesions). And yet the first degree of injury is directly related to type 2 diabetes and patients who have nephropathy, hypertension, neuropathy, dyslipidemia and related diseases, as well as having risk factors such as smoking and alcoholism. Conclusion: Greater investments are needed in health education strategies, strengthening planned investments by a multidisciplinary healthcare team.